"Um Bispo, um Deus, uma ekklesia" : a formação do episcopado monárquico no alto Império Romano - Campos, Ludimila Caliman (2011)
The year of 198 AD is a historic landmark fairly known by the historiography, which dedicates to the history of Christianity. Few pay attention to it was in that year the relations between the Christians communities of Occident and Orient (represented by the congregations of Rome and Gaul, and Asia Minor and Syria-Palestine) were strongly shaken. Eusebius of Caesarea in the work -Ecclesiastical History? narrates that Victor, the bishop of Rome in this period, demanded the Christian communities to gather by region, in order to estipulate a single date for the Easter celebration. While the biggest part of the congregations composed an ecclesiastical decree advocating a similar view for the Easter celebration on Sunday after the fourteenth day of the moon to support Rome, the communities of Minor Asia manifested contrary, being not prepared to leave the Jewish habit to celebrate Easter on the fourteenth day of the moon of Nisan month. In expressing this opinion, the communities of Minor Asia, under the rule of Polycrates, were excommunicated by Victor. Everything suggests that this was the first great schism that is known in the ekklesia. As in any great controversy on both sides appeared leading exponent‘s figures: charismatic leaders asking for an -original? ecclesiastical memory or exercising its power under the justification of a charisma of occupation.? This controversy, known as issue Quartodeciman, was inserted in a vast context of struggles for the power between the bishops in the II century, on both regional and supraregional level, as witnessed the letters of Ignatius of Antioch and the work Against Heresies by Irenaeus of Lyon. Contiguously, a hierarchical structure inside the ekklesia, said to be -orthodox?, was forged during a process of institutionalization and legitimization of the same before the Judaizing, Schismatic and Heretical threats. Under this prism, the object of this research is to understand the formation of the monarchical episcopate in Christian communities of Occident and Orient according to the dynamics of power relations and the institutionalization of political and social -orthodox? ekklesia in the second century.